Cell origin and niche availability dictate the capacity of peritoneal macrophages to colonize the cavity and omentum. Issue 4 (10th May 2022) - Louwe, Pieter A.; Forbes, Stuart J.; Bénézech, Cécile; Pridans, Clare; Jenkins, Stephen J.
Abstract: The relationship between macrophages of the peritoneal cavity and the adjacent omentum remains poorly understood. Here, we describe two populations of omental macrophages distinguished by CD102 expression and use an adoptive cell transfer approach to investigate whether these arise from peritoneal macrophages, and whether this depends upon inflammatory status, the origin of peritoneal macrophages and availability of the omental niches. We show that whereas established resident peritoneal macrophages largely fail to migrate to the omentum, monocyte‐derived resident cells readily migrate and form a substantial component of omental CD102 + macrophages in the months following resolution of peritoneal inflammation. In contrast, both populations had the capacity to migrate to the omentum in the absence of endogenous peritoneal and omental macrophages. However, inflammatory macrophages expanded more effectively and more efficiently repopulated both CD102 + and CD102 − omental populations, whereas established resident macrophages partially reconstituted the omental niche via recruitment of monocytes. Hence, cell origin determines the migration of peritoneal macrophages to the omentum and predisposes established resident macrophages to drive infiltration of monocyte‐derived cells. Abstract : Peritoneal inflammation results in recruitment of long‐lived monocyte‐derived macrophages that, unlike established resident cavity macrophages, readily migrate to and outpopulate omental FALC. These data reveal the complex relationship between peritoneal and omental macrophages, the importance of origin in peritoneal macrophage function, and long‐term effects of inflammation on cavity immune homeostasis